Biosensor - VON GENTZKOW, WOLFGANG; WANNER, GERHARD; FEUCHT, HANS-DIETER; FORMANEK, HELMUT (1997)
A biosensor having a selective detection system composed of a polymer and of a biochemical substance, in particular an enzyme, is characterised by a detection system produced in the following way: - an olefinically unsaturated, epoxy-functional polysiloxane is applied in the form of a film to a carrier material, - the polysiloxane is crosslinked by high-energy radiation to give a wide-mesh epoxy-functional polymer matrix, - the film is treated with an aqueous solution of the biochemical substance, resulting in immobilisation of the biochemical substance by reaction with epoxide groups in the polymer matrix, - the film is stabilised by reaction of unreacted epoxide groups with a compound containing amino and/or carboxyl groups.